PENCAIRAN KREDIT PEMILIKAN RUMAH (KPR) DENGAN JAMINAN PERJANJIAN PENGIKATAN JUAL BELI (PPJB) (ANALISIS STUDI KASUS PUTUSAN NO.1049 PDT.G/2020/PN SBY) - Arofi Fitradani (2023)
The binding sale and purchase agreement (PPJB) basically has not resulted in the transfer of ownership of an object from the seller to the buyer. This stage is only an agreement and must be followed by a levering agreement, namely the signing of the Sale and Purchase Deed (AJB) before the Land Deed Making Officer (PPAT). However, in practice PPJB can be used as collateral for mortgage financing (KPR) by banks in transactions between buyers and developers. 1049 Pdt.G/2020/PN Sby. This research is analyzed by Corrective Justice Theory and Legal Certainty Theory. Using a juridical research method and a statutory and statutory approach as well as a case approach, it is analytically descriptive in nature, the sources of legal materials used are primary, secondary and tertiary legal materials. In this case, inappropriate legal considerations were found including, the PPJB which was signed by the Plaintiff and Defendant I did not include the power of attorney to sell PPJB which resulted in no legal protection and legal certainty for the Plaintiff, the existence of a buyback clause in the PPJB which became the basis of subrogation between Defendants I and II is an act that is prohibited based on the Supreme Court Jurisprudence and the KPR disbursement between the Plaintiff and Defendant II ignores the KPR disbursement procedure regulated in SEBI Indonesia No. 12/ 38 /DPNP.